2008
DOI: 10.1590/s0100-879x2008001200002
|View full text |Cite
|
Sign up to set email alerts
|

Toluene permeabilization differentially affects F- and P-type ATPase activities present in the plasma membrane of Streptococcus mutans

Abstract: Streptococcus mutans membrane-bound P-and F-type ATPases are responsible for H + extrusion from the cytoplasm thus keeping intracellular pH appropriate for cell metabolism. Toluene-permeabilized bacterial cells have long been used to study total membrane-bound ATPase activity, and to compare the properties of ATPase in situ with those in membrane-rich fractions. The aim of the present research was to determine if toluene permeabilization can significantly modify the activity of membranebound ATPase of both F-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Although this was not the aim of the current investigation, it is an interesting approach for evaluation in future studies. Furthermore, a previous study suggested that toluene, which is used for cell permeabilization, may inhibit the activity of F-ATPase (20). This study also suggests that toluene may induce rupture of the cell membrane, causing an outflow of ATPases found in the cytoplasm.…”
Section: S Mutans Genotypesmentioning
confidence: 54%
“…Although this was not the aim of the current investigation, it is an interesting approach for evaluation in future studies. Furthermore, a previous study suggested that toluene, which is used for cell permeabilization, may inhibit the activity of F-ATPase (20). This study also suggests that toluene may induce rupture of the cell membrane, causing an outflow of ATPases found in the cytoplasm.…”
Section: S Mutans Genotypesmentioning
confidence: 54%
“…The regulator CcpA has been implicated in the regulation of the F‐type ATPase (Abranches et al ., ); however, regulation of the ATPase enzymes at the transcriptional level is not well understood. Although it has been hypothesized that the shifts in membrane unsaturation may affect activity of the S. mutans F‐ATPase (Fozo & Quivey, ; MacGilvray et al ., ), measuring ATPase activity in live, intact cells presents a technical challenge (Thedei et al ., ); and, so a link between ATPase activity and the UFA : saturated fatty acids ratio in the S. mutans membrane has yet to be directly confirmed. In E. faecalis , F‐type ATPase activity is regulated at the level of assembly, where a reduction in intracellular pH halts degradation of the complex subunits and allows association of the active enzyme in the membrane.…”
Section: Maintenance Of An Alkaline Cytoplasmmentioning
confidence: 99%
“…30,31,38 Figure 1 shows that PDT abolishes the acidogenic capacity of a S. mutans cell suspension, sustaining the effect of this therapy on bacterial metabolism. 25,38 In addition, when the per se toxicity of RB or of the light applied to a nondye-treated suspension was evaluated, results were similar to those of the controls. That indicates that the decrease of the acidogenic capacity of S. mutans is due to the combination of the dye treatment followed by irradiation (which generates reactive oxygen species) and not to dye or light applied alone.…”
Section: Discussionmentioning
confidence: 68%
“…Then glucose was added to an initial concentration of 50 mmol/L, and the resulting decrease in pH was monitored with a thin-bulb glass pH electrode, reflecting metabolic activities of both samples. 38 …”
Section: Glycolytic Ph-drop Assaymentioning
confidence: 99%